PENERAPAN MODEL DISCOVERY LEARNING DENGAN MEDIA AUDIOVISUAL UNTUK MENINGKATKAN PEMBELAJARAN PENGEMBANGAN HIKAYAT MENJADI CERPEN - Lestari, Kurnia; Sulissusiawan, Ahadi; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe research was based on the lack of studentsâ€™ writing skill. The evidence was seen from the students writing achievement which were mostly below 80 â€“ minimum passing grade score â€“ where the students were less skilled in writing their ideas. Problem in this research is â€œhow is the use, evaluation to see the achievement, and learning constraints by using discovery learning model with audiovisual media?â€ This research aims to investigate the use, evaluation to see the achievement, and learning constraints by using discovery learning model with audiovisual to enhance writing ability in developing saga into short story. Method used was descriptive with Classroom Action Research (CAR) model. Technique used was indirect technique namely observation and documentary study. Tools of collecting data were observation guide namely IPKKG 1 and IPKG 2, and studentâ€™s scoring sheet. Analysis technique used was qualitative descriptive. The results, showed average score in cycle I was 48,64, while in cycle II, the average score was 71,70, and in cycle III, the average score was 83,58. Thus, the writing ability in developing saga into short story by using discovery model learning with audiovisual media is increased from cycle I, II, and III.Â Â Â Â Â Â Â Â Â  . Â Key words: discovery learning model, saga, short story, writing ability.